How to escape a liquidity trap with interest rate rules - Fernando Duarte (Federal Reserve Bank of New York, 2016)
I give necessary and sufficient conditions under which interest-rate feedback rules eliminate aggregate instability by inducing a globally unique optimal equilibrium in a canonical New Keynesian economy with a binding zero lower bound. I consider a central bank that initially keeps interest rates pegged at zero for a length of time that depends on the state of the economy and then switches to a standard Taylor rule. There are two crucial principles to achieving global uniqueness. In response to deepening deflationary expectations, the central bank must, first, sufficiently extend the initial period of zero interest rates and, afterward, follow a Taylor rule that does not obey the Taylor principle. I obtain all results assuming a passive or Ricardian fiscal policy stance, so that it is monetary policy alone that eliminates undesired equilibria. The interest rate rules that I consider do not require central banks to undergo any significant institutional change and do not rely on the Neo-Fisherian mechanism of inducing an increase in inflation by first increasing interest rates.
Keywords: E43; E52; E58; 330; zero lower bound (ZLB); liquidity trap; New Keynesian model; indeterminacy; monetary policy; Taylor rule; Taylor principle; interest rate rule; forward guidance